Extending applied linguistics for social impact cross-disciplinary collaborations in diverse spaces of public inquiry - Warriner, Doris S. 1969-; Miller, Elizabeth R. 1965- (London, UK Bloomsbury Academic, 2023)
"Despite the commitment of applied linguistics research to investigate language use in real-world contexts, applied linguists have struggled to make their work accessible and relevant outside academia. Acknowledging that the field has not yet reached its full potential, this book demonstrates how applied linguists can utilize their knowledge and methods to explore contemporary social problems beyond the borders of their own discipline, to have a valuable impact on other fields, local communities and the general public. Drawing on theories, methods and methodologies in applied linguistics, chapters address pressing concerns such as equal access to education for immigrants, science education in preschool dual-language contexts, healthcare delivery to refugee families, gendered language in disability studies and social sustainability initiatives. The diversity of research contexts shows how the work of applied linguists can have tangible social impact and help to influence meaningful change. By increasing public awareness of language-related issues affecting society, this book responds to a vital gap in the field and marks and important step towards a more socially-engaged, accessible and inclusive approach to applied linguistics"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Applied linguistics -- Social aspects; Language and languages -- Study and teaching -- Social aspects